Use of alternative extender added of fructose aiming the cryopreservation of boar semen - Ludymila Furtado Cantanhêde; Eduardo Nunes de Freitas; Tatyane Bandeira Barros; Daianny Barboza Guimarães; Aline Viana Dias; Ricardo Toniolli (Brazilian Journal of Veterinary Research and Animal Science, 2018)
This study aimed to analyze skimmed milk powder (SMP) and fructose in a new cooling curve to freeze boar semen. A total of 49 semen samples from seven boars were cryopreserved using the new curve with addition of glucose and fructose to the refrigerating diluents: Beltsville Thawing Solution (BTS + G; BTS + F) and Skimmed milk powder (SMP + G; SMP + F), totaling four experimental groups for analysis. To finish the curve, aliquots of semen were packaged in 0.5 ml straws and kept in liquid nitrogen. During the cooling curve, SMP mean spermatic vigor and motility were greater than the BTS (p < 0.05). After thawing, a decrease of spermatic force and motility in both extenders was observed, where the BTS presented spermatic vigor (2.1 ± 0.55) and motility (38 ± 21.8), presenting better results (p < 0.05). There was no statistical difference between sugars added to the BTS and SMP in spermatic force and motility (p > 0.05), although the use of fructose allowed an equalization of motility between the SMP and BTS (p > 0.05). Functionality of membrane was better preserved with the addition of fructose, in both extenders. The rate of sperm viability was significantly higher in extender containing glucose and SMP (71.8 ± 12.5). The percentage of intact acrosome was higher on the treatment containing glucose, independent of the extender (BTS + G: 81.8 ± 7.2, SMP + G: 81.4 ± 14.2). To conclude, the results suggest that the BTS is still the best option to cryopreserve and fructose could be used in boar semen cryopreservation in new cooling curve.